α-Adrenergic Vasoconstriction Contributes to the Age-Related Increase in Conduit Artery Retrograde and Oscillatory Shear - Casey, Darren P. (2012)
Aging is associated with increased retrograde and oscillatory shear in peripheral conduit arteries of humans. Although the mechanisms responsible for these age-related changes are not completely understood, augmented downstream α-adrenergic tone likely plays a significant role in this phenomenon. Therefore, in Protocol 1 brachial artery diameter and blood velocity were measured via Doppler ultrasound during 1) rest (control), 2) endogenous norepinephrine release via intra-arterial infusions of tyramine, and 3) α-adrenergic blockade via infusions of phentolamine in young healthy humans (n=12). Tyramine increased brachial artery retrograde (−4.0±1.4 to −9.5±1.4 s(−1)) and oscillatory shear (0.05±0.02 to 0.18±0.05 arbitrary units), whereas, phentolamine abolished retrograde and oscillatory shear (P<0.05). Additionally, in Protocol 2 we examined brachial artery shear patterns in young (n=12; 29±2 years) and older (n=13; 69±2 years) healthy adults during 1) rest (control), 2) sympathetic activation via lower body negative pressure, and 3) infusion of phentolamine. At rest older adults exhibited greater brachial artery retrograde and oscillatory shear (−9.9±2.7 s(−1) and 0.11±0.03 arbitrary units, respectively) compared with younger adults (−3.1±1.0 s(−1) and 0.05±0.02 arbitrary units, respectively; P<0.05 for both). Lower body negative pressure increased retrograde and oscillatory shear in young (P<0.05), but not older adults (P=0.85–0.97), such that differences between young and older were eliminated (P>0.05). During infusion of phentolamine, retrograde and oscillatory shear were abolished in young adults (P<0.05) and markedly reduced, yet still persistent, in older adults (P<0.01). Our data indicate that α-adrenergic vasoconstriction is a major contributor to age-related discrepancies in conduit artery shear rate patterns at rest.